Understanding Grief During the First-Wave of COVID-19 in the United Kingdom—A Hypothetical Approach to Challenges and Support - Fang, Chao; Comery, Alastair (Frontiers in Sociology, 2021)
Purpose: this article develops immediate understandings of loss and grief at both an individual and collective level following the first-wave of COVID-19 in the UK. This allows for insights into the likely challenges and support for loss and grief in facing unprecedented disruption and uncertainty. Ultimately, it explores avenues for the priorities to inform better bereavement support. Methods: by examining trusted media data and carefully selected academic literature, we analyse both individual and societal responses to loss and grief in the novel context of the first-wave of COVID-19 in the UK. The discussion relocates the ideas of good and bad deaths in the context of increased social constrains and inequalities. Further, two pairs of contrasting hypotheses are proposed to examine how the UK’s first-wave outbreak has shaped policy and practical structures and how these have further impacted experiences of loss and grief both at an individual and collective level. Findings: the discussion captures a mixed picture of loss and grief in the UK, which highlights the importance of timely, holistic and continuous support both in social policy and care provision. It is found that individuals and collectives express diverse needs in response to deaths and losses as a process of meaning-making. Further, the significance of socio-cultural environments also become evident. These findings highlight community support during the outbreak and further promote a grief literate culture as imperative to support individual and collective needs when confronted with loss and grief. Conclusion: this article provides a timely and comprehensive account of possible challenges and support both for individual and collective experiences of loss and grief at a time of unprecedented social restrictions and mass deaths in the UK. These understandings provide a base from which we advocate the priorities for future research into the ongoing impacts of COVID-19 on grief and bereavement.